Rancang Bangun Website Pemasaran dan Penjualan Properti (Study Kasus : PT Indah Cemani Raya) - Harfizar Harfizar; Meri Mayang Sari; Rivaldi Marbun (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
Property sales business is a business activity of buying and selling goods and services related to property (buildings and land). Business in the property sector is a type of business that is quite promising. With the increasing number of competitors in this property business, developers must be more active and innovative in introducing products, so a solution is needed to attract many buyers by using an e-commerce system. The problems faced in this sales system are still in a less broad scope, data management still uses a handwritten media system on a sheet of paper so it takes a long time, and monthly report storage media still uses a ledger that requires accuracy. The designed system produces fast, precise, and accurate information in the entire process, both in terms of data input, transaction processing (orders), to output. The development method used is a prototype model and the PHP programming language so that the website runs dynamically which is supported by a MySQL database. The solution obtained from the above problems is to build a website-based online sales system, so that sellers and buyers do not meet face-to-face. With this system, it is expected to expand the area and facilitate sales marketing and increase and make it easier for the public to get information.